Law Concept related to Limitation Freedom of Contract Marriage Agreement in Indonesia - Liora, Noela; Djumikasih, Djumikasih; Dwi Qurbani, Indah (CV. AFDIFAL MAJU BERKAH, 2024)
In this thesis, the author analyzes the legal obscurity of the limitations on the contents of Marriagel Agreement, which of course has an impact on legal certainty itself, especially regarding the parties' freedom of contract. This is because there is no further explanation regarding the words law, religion and morality in Article 29 paragraph 2 of the Marriage Law, so that if they are defined generally, according to the opinion of experts, they certainly have different meanings. The different meanings of several experts have an impact on the public's lack of understanding regarding these boundaries. Based on this obscurity, the author formulates a problem formulations, what is the ideal concept of setting limits on freedom of contract marriage agreement in indonesia?. The research method used in writing this thesis uses conceptual approach, statute approach and comparative approach by making a comparison with California. Using this method, it can be concluded that Regulations related to marriage agreements need to be amended regarding the regulation of limitations on the contents of marriage agreements, because there have been cases due to the extensive limitations on the contents of marriage agreements in Indonesia which have created uncertainty regarding marriage agreements. There are several concepts for changes in the regulation of marriage agreements in Indonesia, namely the existence of special regulations, the distinction between prenuptial agreements and marriage agreements, and the creation of details related to limitations.